2021
DOI: 10.1038/s41598-021-93353-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural hazard triggered technological risks in the Yangtze River Economic Belt, China

Abstract: With the continuous occurrence of natural disasters, natural hazard triggered technological accident (Natech) risks also follow. At present, many countries have performed much research on Natech risks. However, there is still a lack of Natech research at the regional or watershed level in China. The Yangtze River Economic Belt (YREB) is not only an industrially intensive development area but also an area with frequent natural disasters. In this study, we selected the YREB as a typical case to study the Natech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In addition, flood disasters could trigger natural hazards. Gao et al (2021) found that the risks triggered by flood disasters were concentrated in the eastern area and central area [40]. Considering the impacts of climate change, the extreme precipitation had increasing trends in the middle and lower reaches of the YREB [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, flood disasters could trigger natural hazards. Gao et al (2021) found that the risks triggered by flood disasters were concentrated in the eastern area and central area [40]. Considering the impacts of climate change, the extreme precipitation had increasing trends in the middle and lower reaches of the YREB [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The mountainous and hilly landforms in the Yichang section of the Yangtze River Basin are widely distributed. The geological environment is very fragile, and there are many geological disasters such as landslides, collapses, and debris flow [7][8][9]. Especially along the Three Gorges Reservoir area, the development of geological disasters is more intense, which poses a threat to urban construction and residents' production and life [10].…”
Section: Introductionmentioning
confidence: 99%